Food, national identity and tourism in Greenland. - Ren, Carina; Fusté-Forné, Francesc (Food, Culture & Society, 2024)
This article explores the dynamic relationship between food, national identity and tourism in the context of Greenland, showing how food contributes to identity development and how in turn identity communication fuels tourism attraction and gastrodiplomacy. In the following, we first offer a review of current literature on national food identity and introduce Greenland, an Arctic nation moving toward independence from the kingdom of Denmark, as an interesting and understudied field of study. Drawing on four case narratives, we describe different food tourism situations which illustrate four examples of Greenlandic food practices. In our analysis of Greenlandic food experiences, we show the coexistence of different Greenlandic food practices in the tourism offer: food as traditional, as natural, as hybrid and as innovative. In our conclusion, we come back to the issue of national identity, discussing the role of tourism in maintaining and constructing food identities in Greenland.